EXTRACTION OF COPPER AND NICKEL FROM SOLUTIONS FOLLOWED BY EXTRACTION OF NICKEL WITH DIMETHYLGLYOXIME - Shodiev , Abbos Ne’matugli; Gayratova , Madinabonu Zakhriddinkizi (Sanoatda raqamli texnologiyalar, 2024)
Nickel has many excellent properties including ductility, corrosion resistance, magnetism, stability and high temperature stability which plays an important role in the development of key industries. Accordingly, at the first stage of the research, the direction of research, the possibilities of extracting metals from solutions by ion flotation and extraction were determined, and mother liquors of the vitriol workshop were selected. The chemical composition of the mother liquor of the vitriol plant was determined as a result of the research, the use of naphthenic acid in ion flotation and the dependence of the duration of flotation on the extraction of metal, as well as the methodology of its extraction, were drawn up.